CAMERON LESIONS: LITERATURE REVIEW AND CASE PRESENTATION - V. V. Vasilenko; D. L. Vinogradov; M. S. Khamidulina (SINAPS LLC, 2016)
Cameron syndrome is the ulcerative or erosive lesions of mucosal layer at the sac of hiatal hernia which can cause chronic occult or overt bleeding and iron-deficiency anemia. Hiatal hernia is a relatively frequent finding, which is in most cases asymptomatic or manifested by dyspeptic symptoms of varying severity. Despite of being a very important association of hiatal hernia Cameron syndrome is not widely represented in medical literature. That`s the reason of a lack of awareness among physicians, surgeons and endoscopists about that pathology. Cameron lesions are significant pathology because they can become a source of chronic occult as well as an acute life-threatening bleeding. Those lesions of upper gastrointestinal tract are often misinterpreted or overlooked during standard diagnostic procedures. It can lead to the misdiagnosis and false ways of treatment. The review focuses on the pathogenesis, main diagnostic problems and treatment options of that pathology. The diagnostics of the Cameron syndrome is difficult because sometimes the lesions can`t be seen on upper gastrointestinal tract endoscopy. The review describes the criteria by which the physician may suspect Cameron syndrome when endoscopy results are not certain. Clinical case represents an important problem which is often faced by the doctors - the severe iron-deficiency anemia refractory to the medication and blood transfusions in the patients with Cameron lesions. It`s very important for doctor to be aware of that complication to include Cameron syndrome into the diagnostic search for the sources of persistent blood loss. Cameron lesions can be asymptomatic as well as be manifested in the form of severe chronic anemia. And that`s the reason why there are an important issue about the proper treatment which have to be provided in each case. The review describes the effectiveness of different treatment options and makes the conclusion about the principles on which doctor can rely in giving favor to a conservative or surgical treatment.